A validated UPLC-MS/MS assay for the quantification of amino acids and biogenic amines in rat urine - Gray,N; Plumb,RS; Wilson,ID; Nicholson,JK (Journal of Chromatography B: Analytical Technologies in the Biomedical and Life Sciences, 2019)
A UPLC-MS/MS assay, employing a reversed-phase separation, has been applied to the analysis of a number of common amino acids and biogenic amines in rat urine. Analytes were derivatised, using 6aminoquinolylNhydroxysuccinimidyl carbamate (AccQTag Ultra™). Derivatisation with this reagent, by increasing the hydrophobicity of the analytes, enables better retention by improving reversed-phase chromatographic properties and also improves ionisation efficiency to enhance MS-detection. The method allows for the determination of 38 amino compounds in 7.5min, including baseline resolution of critical isomers. The assay has been validated for the absolute quantification of 29 amino compounds in rat urine, over a concentration range of 0.6–200μM, for the purpose of exploratory metabolite phenotyping. Acceptable linearity (R2>0.995) and intra- and inter-day accuracy (<20.7%) and precision (<20.1%) for these analytes was achieved. The limits of detection ranged from 1.2–12fmol on column with 20μL of sample. The remaining nine amines examined were not accurately quantified by this method but can be monitored for relative/fold change in biological samples. The use of the method is exemplified by the monitoring of changes in healthy male Sprague-Dawley rat urinary amino acid concentrations over a 7-day period.